Investigation of Doxorubicin Efficiency in Some Hematological Parameters in Women with Breast Cancer in Iraq - Hanan B. Saadon (University of Thi-Qar Journal of Science, 2024)
Breast cancer is a prevalent disease among females worldwide. Low levels of doxorubicin are used as a standard treatment, predicting severity, mortality, and treatment compliance. This study aims to explore differences in hematological profiles and effects of doxorubicin in breast cancer patients. A descriptive cross-sectional study in Thi-Qar province compared the hematological parameter of the forty Female Breast Cancer patients. Patients’ data were then grouped according to four categories: chemotherapy sessions. It will take 8 months of chemotherapy and will involve one session every 21 days. The results showed that the patients had an average white blood cell count of 5.85, lower than the control group’s 8.8, and a mean hemoglobin of 10.99. The patient group had a mean platelet count of 321.7, higher than the control group’s 251.4, indicating a statistically significant difference at a significance level of α ≤ 0.05. Doxorubicincontinues to be used in the management of breast cancer; nonetheless, its utilization is limited because of toxicity, including cardiotoxicity and myelosuppression. As it is with tradition in advanced breast cancer, the vast majority of the submitted patients experienced some form of hematological alteration, which includes anemia, leucopenia, and thrombocytosis. Hematologic studies are thus very relevant in breast cancer management, its progression, and also in detection of some sequential malignancies related to breast cancer.